Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\sqrt{x^2-4x+4}=3\Leftrightarrow\sqrt{\left(x-2\right)^2}=3\)
\(\Leftrightarrow x-2=3\Leftrightarrow x=5\)
b, \(\sqrt{x^2-10x+25}=x+3\Leftrightarrow\sqrt{\left(x-5\right)^2}=x+3\)
\(\Leftrightarrow x-5=x+3\Leftrightarrow0\ne8\)( vô nghiệm )
a) \(\sqrt{4\left(a-3\right)^2}=\sqrt{2^2\left(a-3\right)^2}=2\sqrt{\left(a-3\right)^2}=2.\left|a-3\right|=2\left(a-3\right)=2a-6\) (Vì \(a\ge3\) )
b) \(\sqrt{9\left(b-2\right)^2}=\sqrt{3^2\left(b-2\right)^2}=3\sqrt{\left(b-2\right)^2}=3\left|b-2\right|=3\left(2-b\right)\)
\(=6-3b\) (vì b < 2 )
b) \(\sqrt{27.48\left(1-a\right)^2}=\sqrt{27.3.16.\left(1-a\right)^2}=\sqrt{81.16.\left(1-a\right)^2}\)
\(=\sqrt{9^2.4^2.\left(1-a\right)^2}=9.4\sqrt{\left(1-a\right)^2}=36.\left|1-a\right|=36\left(1-a\right)=36-36a\) (vì a > 1)
Đáp án C
Thay y = 3 vào hàm số ta được: f(3) = 3 3 - 3.3 - 2 = 16 ⇒ 2.f(3) = 2.16 = 32.